GeoGebra Assisted Multiple Representations for Enhancing Students’ Representation Translation Abilities in Calculus - Arefaine, Nigusse; Michael, Kassa; Assefa, Shimelis (Asian Journal of Education and Training, 2022)
Multiple representations cultivate students’ mathematical mindset. However, research results have reported that students do not benefit from these tools due to lack of representational fluency. This study was designed to determine the impact of GeoGebra assisted multiple representations approach on students’ representation translation performance in calculus. Pretest - posttest quasi experimental design was implemented. Three intact groups of first year first semester of social science students in the 2019/2020 academic year of size 53, 57 and 54 at Jigjiga and Kebri-Dehar Universities in Ethiopia were considered. The groups were taught with GeoGebra supported multiple representations (MRT), multiple representations (MR) and comparison group (CG). Representation translation test was given before and after the treatment. Furthermore, students’ translation errors were categorized as implementation, interpretation and preservation errors and analyzed using frequency and percentage. The ANCOVA result revealed that significant difference was obtained on the adjusted mean of RTF posttest (F (2,160) = 5.29, P = 0.006, Partial η2 =0.062) in favor of the MRT. The interpretation error was the most frequently committed among the groups. Recommendations were forwarded that included the use of GeoGebra and the need to conduct further study with different participants to generalize to the entire population.